MG53 attenuates nitrogen mustard‐induced acute lung injury. Issue 7 (24th February 2022) - Li, Haichang; Rosas, Lucia; Li, Zhongguang; Bian, Zehua; Li, Xiuchun; Choi, Kyounghan; Cai, Chuanxi; Zhou, Xinyu; Tan, Tao; Bergdall, Valerie; Whitson, Bryan; Davis, Ian; et al.
Abstract: Nitrogen mustard (NM) is an alkylating vesicant that causes severe pulmonary injury. Currently, there are no effective means to counteract vesicant‐induced lung injury. MG53 is a vital component of cell membrane repair and lung protection. Here, we show that mice with ablation of MG53 are more susceptible to NM‐induced lung injury than the wild‐type mice. Treatment of wild‐type mice with exogenous recombinant human MG53 (rhMG53) protein ameliorates NM‐induced lung injury by restoring arterial blood oxygen level, by improving dynamic lung compliance and by reducing airway resistance. Exposure of lung epithelial and endothelial cells to NM leads to intracellular oxidative stress that compromises the intrinsic cell membrane repair function of MG53. Exogenous rhMG53 protein applied to the culture medium protects lung epithelial and endothelial cells from NM‐induced membrane injury and oxidative stress, and enhances survival of the cells. Additionally, we show that loss of MG53 leads to increased vulnerability of macrophages to vesicant‐induced cell death. Overall, these findings support the therapeutic potential of rhMG53 to counteract vesicant‐induced lung injury.